FACTORS ASSOCIATED WITH FIBROSIS IN CHRONIC HEPATITIS C PATIENTS - Zaki, Madiha; Memon, Sadik; Jiskani, Saddat Ali; Qadir, Bushra; Chaang, Adil (Annals of Allied Health Sciences, 2024)
Objective: To identify the factors associated with fibrosis progression in a Pakistani cohort of Chronic hepatitis C (CHC) patients. Material & Methods: A retrospective study was conducted at the Asian Institute of Medical Sciences, Hyderabad involving 350 CHC patients diagnosed between 2021 and January 2024. Data on demographics, clinical characteristics, and laboratory findings were collected. Fibrosis severity was assessed using non-invasive markers (FIB-4 index, APRI score), transient elastography, and, where available, liver biopsy reports. Multivariate logistic regression analysis was performed. Results: The mean age of participants was 45.2 years, with a male predominance (62.3%). Advanced age (>50 years) was significantly associated with severe fibrosis (OR 2.34, p = 0.001). Other factors linked to advanced fibrosis included male gender (OR 1.89, p = 0.017), HCV genotype 3 (OR 2.61, p < 0.001), prolonged infection duration (>10 years, OR 1.75, p = 0.021), insulin resistance (HOMA-IR >2.5, OR 2.95, p < 0.001), alcohol consumption (OR 3.12, p < 0.001), and co-infection with HBV or HIV (OR 2.58, p = 0.003). Conclusion: This study identifies critical factors influencing fibrosis progression in CHC patients in Pakistan. Targeted monitoring and management of high-risk groups, along with early diagnosis and timely intervention, can help mitigate complications and improve patient outcomes. Public health efforts should prioritize these strategies to address the burden of CHC-related fibrosis.